2013
DOI: 10.1002/ajmg.a.35756
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes regarding a pilot study of newborn screening for spinal muscular atrophy

Abstract: A population-based pilot study of newborns screening for a rare genetic condition, spinal muscular atrophy (SMA), is being conducted with funding from the National Institutes of Health. The first component of the study is to assess the ethical, legal and social implications of population-based pilot studies with a focus on public engagement and parental decision-making for the proposed opt-out approach in this research. We conducted focus groups with members of the general public to ascertain attitudes about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…All studies were observational; none employed experimental or quasi-experimental designs. Eleven studies used qualitative or survey methods to obtain input from patients, 4,7,[18][19][20][21][22][23][24][25][26] and 17 studies were narrative reports describing one group's experiences with engagement. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The remaining seven studies were descriptions of specific initiatives reported on websites [44][45][46][47][48][49][50] ( Table 1 and Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were observational; none employed experimental or quasi-experimental designs. Eleven studies used qualitative or survey methods to obtain input from patients, 4,7,[18][19][20][21][22][23][24][25][26] and 17 studies were narrative reports describing one group's experiences with engagement. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The remaining seven studies were descriptions of specific initiatives reported on websites [44][45][46][47][48][49][50] ( Table 1 and Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…cians. 20,38,39,47,49 Seven studies were classified as sufficiently descriptive 7,18,19,[23][24][25][26] The purposes of engagement included identifying patient-centered research topics or agendas, 19,23,29,36,39 identifying outcomes important to patients or developing measures relevant to patients' needs, 7,19,20,23,25,26 increasing recruitment or enrollment through development of patient-centered study designs, 4,18,21,24,27,30,31,41 and incorporating the patient perspective into study design 19,25,35,39,40 (Table 2, Table 3). Patients and other stakeholders were most commonly engaged in the preparatory stage (n= 19 for agenda setting) 4, 7, 19, 20, 23, 25, 28, 29, 32, 35, 36, 39- (Table 4 [online]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,31,32 The idea of newborn screening has a high level of support among parents of children who have SMA and among expecting parents. 33,34 A long delay to diagnosis has been noted in other pediatric diseases as well. For example, a median delay of 1.4 months to 12.6 years from symptom onset to diagnosis has been noted in patients with Pompe disease, 35 whereas a delay of 6 months to more than 4 years has been documented in patients with Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 97%